محنة الاغتراب عند بطل رواية (كيف ترضع من الذئبة دون أن تعضك) للروائي عمارة لخوص - هميسي, عبد الرشيد (جامعة الوادي - university of Eloued, 2022)
يتناول هذا المقال تيمة معاصرة مهمة أخذت تتفحل وتطغى على كثير من الكتابات السردية ألا وهي تيمة الاغتراب. ومفهوم الاغتراب قديم جديد كان منذ وجد الإنسان على أرض البسيطة , لكنه أخذ يكبر ويشتد كلما نزع الإنسان نحو الحضارة والمدينة لأن من شأن هذه الأخيرة أن تولده بقوة فلقد غدا أحد سيماتها , فنستطيع القول أن الاغتراب بجميع أنواعه وعبر كل أصعدته وتجلياته هو ابن الحضارة والمدنية, وهذا الأمر من شأنه أن يُفرض على جنس الرواية باعتباره الجنس الممثل الأول للإنسان المتحضر, فهو أقرب الأجناس تمثيلا لهمومه وقضاياه وتطلعاته. وبما أن في الجزائر روائيون صوبوا وجوههم قِبَل الغرب, فاغتربوا وعانوا ما يعانيه المهاجر , اضرهم ذلك للكتابة في هذا الموضوع . ومن هؤلاء الروائي عمارة لخوص الذي كتب روايته المشهورة (كيف ترضع من الذئبة دون أن تعضك). تناول في هذه الرواية محنة الاغتراب التي يعاني منها الإنسان غير الإيطالي في إيطاليا بما فيهم الفرد الجزائري, والذي مثله بطل الرواية أميديو. طرقنا في هذا المقال مفهوم الاغتراب وأنواعه وتجلياته في البطل أميديو , متتبعين في ذلك تسلسل الأحداث ودورها في كشف حقيقة البطل الذي اختفى في هوية إيطالية لكي يستطيع العيش في روما, والنص مليء بصراع الهويات. الكلمات المفتاحية: الاغتراب؛ كيف ترضع من الذئبة؛ عمارة لخوص؛ رواية؛ الهجرة. Abstract: This article deals with an important contemporary theme that is beginning to flourish and dominate many narrative writings, which is the theme of alienation. The concept of alienation is old and new, since man was found on earth, but it began to grow and intensify as man moved towards civilization and the city, because the latter would generate him strongly. This matter would be imposed on the genre of the novel as the gender that is the first representative of civilized man, as it is the closest race to represent his concerns, issues, and aspirations. And since there are novelists in Algeria who turned their faces towards the West, so they became alienated and suffered what the immigrant suffers from, and that compelled them to write on this subject. Among them is the novelist Amara Lakhous, who wrote his famous novel (How to Breastfeed from Lupus Without It Bite You). In this novel, he deals with the plight of alienation suffered by non-Italian people in Italy, including the Algerian individual, who is represented by the protagonist, Amedeo. In this article, we discussed the concept of alienation, its types, and its manifestations in the hero Amedeo, tracing the sequence of events and their role in revealing the truth about the hero who hid in an Italian identity in order to be able to live in Rome, and the text is full of conflict of identities. Alienation, how to breastfeed from lupus, amara lakhous, a novel, migration Key words: Alienation, how to breastfeed from lupus, Amara lakhous, a novel, migration.
مقال
Keywords: الهجرة ; عمارة لخ ; ص ; ر ; اية ; كيف ترضع من الذئبة ; اغتراب